Green Intellectual Capital and Circular Economy Practices for Sustainable Competitive Advantage: A Covariance-Based Structural Analysis of Manufacturing Firms - Gianluca Zammit (Oikonomia Review: A Journal of Applied Management, Accounting, and Business Strategy, 2026)
This study investigates the structural pathways linking green intellectual capital and circular economy practices to sustainable competitive advantage within the manufacturing sector. A deductive quantitative research design was deployed, collecting empirical survey data from 412 senior operations and sustainability executives managing large-scale manufacturing facilities. Covariance-based structural equation modeling was executed within the IBM SPSS AMOS environment to evaluate the psychometric properties of the measurement framework and test the direct and indirect structural path hypotheses via maximum likelihood estimation. The structural model confirmed that Green Intellectual Capital exerts a significant positive effect on Circular Economy Practices (β = 0.542, p < 0.001) and Sustainable Competitive Advantage (β = 0.318, p < 0.001). Circular Economy Practices also demonstrated a strong positive influence on Sustainable Competitive Advantage (β = 0.456, p < 0.001). The indirect effect of Green Intellectual Capital on Sustainable Competitive Advantage through Circular Economy Practices was statistically significant (β = 0.247, p < 0.001), indicating partial mediation. The proposed structural model achieved satisfactory goodness-of-fit, with χ²/df = 1.782, Comparative Fit Index (CFI) = 0.968, Tucker-Lewis Index (TLI) = 0.961, Root Mean Square Error of Approximation (RMSEA) = 0.043, and Standardized Root Mean Square Residual (SRMR) = 0.038. These findings suggest that manufacturing firms can strengthen their sustainable competitive advantage by integrating green intellectual capital with circular economy practices, enabling environmental knowledge and organizational capabilities to be translated into long-term strategic value.